Hepatocyte aquaporins in bile physiology and disease - Marinelli, Raúl A. (2016)
Bile formation by hepatocytes is an osmotic secretory process resulting from the canalicular secretion of water in response to osmotic gradients created by the active transport of solutes, primarily bile salts, and other organic anions. Thus bile secretion would be ultimately dependent on the canalicular expression of bile salt and organic anion transporters as well as the osmotic water permeability of the canalicular plasma membrane domain, mainly determined by aquaporin-8 (AQP8) water channels. Compelling experimental evidence suggests that canalicular AQP8 facilitates the osmotically-coupled transport of solute and water during the formation of bile. Downregulation of AQP8-mediated hepatocyte canalicular water permeability is found in rat models of hepatocellular cholestasis suggesting that defective hepatocyte AQP8 expression is involved in the molecular mechanisms of bile secretory failure. The study of AQP function in liver has provided new insights into normal bile physiology and disease mechanisms, and may yield novel therapies to improve certain cholestatic conditions.